Маркетинг нематеріальної і матеріальної сфер: різниця й специфіка - Ткачук (Стахурська), Світлана Валеріївна; Стахурський, Валерій Олександрович (My University, 2022)
У статті розглядається різниця маркетингу сфери послуг та маркетингу сфери матеріального виробництва. Також пропонується поділ маркетингу за сферами використання на чотири види: маркетинг сервісної сфери В2В, маркетинг сервісної сфери В2С, маркетинг матеріального виробництва В2В та маркетинг матеріального виробництва В2С. Показана різниця маркетингу матеріальної сфери від маркетингу сервісної сфери в аспекті таких категорій як маркетинг, маркетинг-мікс, якість, матеріальність і відчутність, час виробництва і споживання. Щодо кожної категорії перераховані необхідні дії маркетолога, що працює у сфері послуг. Акцентується на особливостях послуги як товару, із яких випливають специфічні риси маркетингу послуг: невідчутність, невіддільність від джерела, непостійність та не збереженість послуги. Як результат особливостей послуг виникає необхідність формування політики не лише зовнішнього й внутрішнього маркетингу, але й інтерактивного маркетингу, тобто маркетингу взаємодії клієнт/персонал у процесі обслуговування. Невідчутність та нематеріальність послуги посилює роль довіри до виробника та значення елементу «фізичний доказ» у системі маркетинг-міксу сервісної сфери, а перед рекламістом і розробником сайту стоїть завдання максимальної візуалізації послуги. Не збереженість послуги вимагає від маркетолога вміння оперативно управляти попитом, протягом не лише року чи місяця, але й днів тижня чи годин доби, а також мистецтво пристосовуватись до попиту у години пік. Мінливість якості послуги потребує чітких стандартів сервісу у поєднанні із мотивацією і навчанням. Втім сучасні технології дозволяють зменшити дію людського чинника і значно усунути негативні прояви особливостей послуг. Крім поділу маркетингу на сервісну сферу і сферу матеріального виробництва, у статті пропонується поділ галузей та сфер на три укрупнені групи: емоційного спрямування, раціонального спрямування та змішаного спрямування. Сутність елементів маркетинг-міксу та їх вагомості можуть коливатися залежно від конкретної групи. The article examines the difference between marketing of services and marketing of material production. It is also proposed to divide marketing by application into four types: B2B service sphere marketing, B2C service sphere marketing, B2B material production marketing and B2C material production marketing. The difference between the marketing of the material sphere and the marketing of the service sphere in terms of such categories as marketing, marketing mix, quality, materiality and tangibility, time of production and consumption is shown. For each category, the necessary actions of a marketer working in the service sector are listed. Emphasis is placed on the features of the service as a product, from which the specific features of service marketing emerge: intangibility, inseparability from the source, impermanence and non-preservability of the service. As a result of the specifics of services, there is a need to formulate a policy not only of external and internal marketing, but also of interactive marketing, i.e. marketing of client/staff interaction in the service process. The intangibility and immateriality of the service strengthens the role of trust in the manufacturer and the importance of the "physical evidence" element in the system of the marketing mix of the service sector, and the advertiser and the site developer face the task of maximally visualizing the service. Service continuity requires marketers to be able to manage demand quickly, not only during the year or month, but also days of the week or hours of the day, as well as the art of adapting to demand during peak hours. The variability of service quality requires clear service standards combined with motivation and training. It is accepted to distinguish separately the quality of the service process and the quality of the result from the purchase of the service. This model was called the functional-instrumental model of service quality, and it does not lose its relevance these days. Modern technologies make it possible to reduce the effect of the human factor and significantly eliminate the negative manifestations of service features. Automation, involving the client in self-service are effective tools for reducing the variability of service quality. Such methods are widely used in retail, banking, partly in education and medicine, and in many other areas and industries. In addition to the division of marketing into the service sphere and the sphere of material production, the article proposes the division of industries and spheres into three consolidated groups: emotional direction, rational direction, and mixed direction. The essence of the elements of the marketing mix and their importance may vary depending on the specific group. Similarly, the ratio of the importance of functional and instrumental quality of the service will depend on the emotional or rational direction of the service.
Keywords: маркетинг; маркетинг сервісної сфери; маркетинг послуг; маркетинг галузей та сфер; маркетинг-мікс сервісної сфери; інтерактивний маркетинг; функціонально-інструментальна модель якості послуг; marketing; marketing of the service sphere; marketing of services; marketing of industries and spheres; marketing mix of the service sphere; interactive marketing; functional-instrumental model of service quality; кафедра маркетингу